PERNIKAHAN CAMPURAN SUNDA-JAWA : ANTARA TRADISI DAN MITOS DALAM PRESPEKTIF MASYARAKAT MODERN - Nazwa Wafiq Nur Azizah; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
Social interaction is very important in everyday life. Social interaction is needed to create social relationships between individuals and individuals or between groups with one another. In a community group, there is an inter-ethnic relationship that is manifested as a relationship between individuals or between ethnic community groups with one another who live as neighbors and get along with each other. This study aims to explore the perspective of modern society in addressing the mythical phenomenon of the prohibition of marriage between Javanese and Sundanese. This descriptive research describes the phenomenon of marriage prohibition based on data collection through literature study. Data analysis is carried out starting from the stage of collecting heirloom data, reading, writing, and managing research literature. The results show that the discourse or myth about Sundanese people who cannot marry Javanese is a historical story that has multiple interpretations. Do not let us be consumed by issues that are not clear the truth, so that it will damage the future of the nation's next generation. It is necessary to instill each other's identity in accordance with the motto of our country which means although different but still one.